2007
DOI: 10.1080/02841860600812693
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms inXPD,XPCand the risk of death in patients with urinary bladder neoplasms

Abstract: Polymorphisms in XPD, XPC and the risk of death in patients with urinary bladder neoplasms, Acta Oncologica, 46:1, 31-41,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…[32] recurrence risk and cancer-specific survival [20]. These findings may have important clinical implications for predicting BCG response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[32] recurrence risk and cancer-specific survival [20]. These findings may have important clinical implications for predicting BCG response.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have also shown NER genes including XPD to be associated with Individuals with variant XPD haplotypes were more susceptible to bladder cancer. The effect was magnified when smoking was considered [24] Bladder cancer Sweden Patients carrying the variant allele of XPD (K751Q) polymorphism were at lower risk of death than the noncarriers [20] Bladder cancer Japanese Combined genotypes with at least one variant allele in XPD or XRCC1 were significantly associated with improved cancer-specific survival compared with remaining groups [25] Cancer (A metaanalysis study)…”
Section: Discussionmentioning
confidence: 99%
“…GarciaClosas et al [14] reported that subjects carrying the heterozygous XPC Lys939Gln genotype were at a significantly higher risk of developing bladder cancer. Sanyal et al reported that homozygotes for the 939Gln allele were found to significantly increase the risk of bladder cancer [13,15]. Chen et al [16] reported that attenuated expression of XPC is associated with critical events in human bladder cancer carcinogenesis and progression.…”
Section: Introductionmentioning
confidence: 97%
“…There are numerous case-control studies on XPC Lys939Gln and its role in urinary bladder cancer susceptibility [13]. GarciaClosas et al [14] reported that subjects carrying the heterozygous XPC Lys939Gln genotype were at a significantly higher risk of developing bladder cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Sanyal et al (2007) indicated that variant allele carriers of the XRCC1 polymorphism showed a lower risk of recurrence (Stage TaG2; P = 0.05) and death (Stage T2 or greater; P = 0.03) after instillation and radiotherapy compared to non-carriers. Sakano et al (2006) showed that for patients with bladder cancer after platinum-based chemoradiotherapy, combined genotypes with at least one variant allele in XRCC1 were significantly associated with improved cancer-specific survival compared with the remaining groups.…”
Section: Discussionmentioning
confidence: 98%